Effects of Three Preseason Training Programs on Speed, Change-of-Direction, and Endurance in Recreationally Trained Soccer Players - Koral, Jérôme; Lloria Varella, Jaume; Lazaro Romero, Fernando; Foschia, Clément (Frontiers in Physiology, 2021)
Background: Modern coaches experience a drastic reduction of the available training time with an increasingly large number of competitions during the competitive season. Thus, they must choose wisely the most efficient methods to improve the physical fitness of their players during the pre-season. Among all the methods, this study compared the effects of a plyometric training (PT), a sprint interval training (SIT) and small sided games (SSGs) on recreationally trained soccer players’ performance. Methods: 73 participants were randomly assigned in one of the three experimental groups (i.e. PT, SIT or SSGs) and completed two sessions per week for a total of three weeks. Meanwhile, the whole group maintained their habitual soccer-specific training program to do not interfere in the preparation of the season. Repeated sprint ability (RSA), maximal aerobic speed (MAS) and a 30 m sprint were assessed at baseline (PRE) and post-training (POST). Results: Performance in SSGs decreased for the average speed from 0 to10 m (V0-10 m; -4 ± 5%, p<0.001), the maximal distance (Dmax) covered in the 30 s RSA test (-3 ± 6%, p<0.01) and maximal aerobic speed (MAS; -3 ± 6%, p<0.01). PT increased the mean distance (Dmean) covered in the 30 s RSA test (5 ± 4%, p<0.001) and MAS (7 ± 5%, p<0.01) while an improvement of all parameters but the maximal sprint speed reached during the 30m trip (Vmax) was found in SIT group (V0-10 m: 8 ± 5%, p<0.001; Dmax: 6 ± 5%, p<0.001; Dmean: 7 ± 5%, p<0.001 and MAS: 12 ± 8%, p<0.001). All SSGs POST values were lower than PT and SIT. Dmean and MAS in POST were also higher in SIT than in PT group. Conclusion: The current study demonstrates that both PT and SIT are a better alternative to SSGs to boost performances during pre-season. Moreover, SIT appears to produce higher improvements on physical performances than PT.